Impact Analysis of Using Gadgets on Imitating Behavior in Early Childhood - Manurung, Verawati; Jamain, Ririanti Rachmayanie; Sari, Nina Permata (Formosa Journal of Applied Sciences, 2024)
This research aims to describe the impact of gadget use on the imitative behavior of early childhood in Santa Maria Integrated Preschool and Kanaan Christian Integrated Preschool Banjarmasin. This research uses a descriptive qualitative approach to multi-site design, with data collection through interviews, observation and documentation. The data analysis stage involves two stages, namely site data analysis and cross-site data analysis. The results of the research are 1) positive impact: increased imagination and self-confidence; hone cognitive and social intelligence; and develop reading, numerical and problem solving skills. 2) negative impact: decreasing concentration and feeling lazy about learning to write and read without gadgets; worsens sociability; harm health and trigger addiction; and hinder progress in cognitive and language development.